Relationship between Strategic Leadership of the School Directors and Academic Administration of Schools under the Prawet District Office, Bangkok - Pantong, Nattakarn (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to: 1) study strategic leadership of school directors under the Prawet District Office, Bangkok Metropolitan Administration; 2) study academic administration in the schools; and 3) study relationship between strategic leadership of the school directors and academic administration in the schools under the Prawet District Office, Bangkok Metrpolitan Administration. It was a qusntitative research using survey method by which a questionnaire was used as an insrumement. A sample of 234 was randomly drawn from administrators and teachers of schools under the Prawet District Office, Bangkok Metropolitant Administration, in the 2023 academic year, using a table of Krejcie & Morgan (1970) which was of minimum criterion, by means of stratified sampling. The data collected using the questionnaire were discriptively analyzed in terms of frequency, percentage, mean, standard deviation, and Pearson's Correlation Coefficient. The results of the research were: 1) strategic leadership of school directors under the Prawet District Office, Bangkok, was overall at the very high level; 2) overall academic administration of the schools was also at the very high level; and 3) overall relationship between strategic leadership of the school directors and academic administration in the schools was positive at the very high level with statistical significance.